2021
DOI: 10.1021/acs.langmuir.1c01723
|View full text |Cite
|
Sign up to set email alerts
|

Electrografting and Langmuir–Blodgett: Covalently Bound Nanometer-Thick Ordered Films on Graphite

Abstract: We present two different molecular organizations obtained from octadecylamine (ODA) molecules on a highly oriented pyrolytic graphite (HOPG) surface: (i) self-organized physisorbed ODA molecules lying flat on the surface and (ii) a strongly electrografted compact crystalline monolayer of ODA molecules standing up on the surface. This new structure is obtained by combining the Langmuir−Blodgett transfer of an ODA Langmuir film onto HOPG with oxidative electrografting. The presence of an organic film on HOPG is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Researchers have reported that the chemical modification method can drive DNA ordered assembly. For example, the ordered lamellar molecular structures formed by ODA can serve as rails for DNA straightening. The electrostatic interactions between the phosphate of DNA and oppositely charged head groups of the ODA layer become predominant and drive the assembly of the DNA molecules .…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have reported that the chemical modification method can drive DNA ordered assembly. For example, the ordered lamellar molecular structures formed by ODA can serve as rails for DNA straightening. The electrostatic interactions between the phosphate of DNA and oppositely charged head groups of the ODA layer become predominant and drive the assembly of the DNA molecules .…”
Section: Introductionmentioning
confidence: 99%